OCCUPATIONAL STRESS AS RISK FACTORS OF SUBJECTIVE FATIGUE FOR WORKERS IN WEAVING LOOM UNIT PT. X - Yulia Dwi Andarini (Universitas Darussalam Gontor, 2017)
An occupation with a high risk of work fatigue is an occupation in textile industry. The involvement of women in the textile industry sector in Indonesia is dominant. Women labors who run work on domestic and public sector will be less inclined a work fatigue. Subjective fatigue is the problem faced by women workers at production division weaving loom unit of PT. X. This study aimed to determine occupational stress that could cause subjective fatigue in weaving loom unit PT. X.Type of this observational analytic study was using a cross sectional design. The number of research subject were 95 people. An occupational stress is independent variable. The dependent variable is a subjective fatigue. Occupational stress measurement was using job stress indicator questionnaire. Subjective fatigue measurement was using Subjective Self Rating Test questionnaires. The effect of strength is calculated by using Odds Ratio (OR) from bivariate analysis. Chi square test used as significance test. All test used 95% confidence interval and significance level of p 0,05.Result: Chi square test result showed that occupational stress has significant association with subjective fatigue. Women workers with moderate occupational stress has higher risk of subjective fatigue more than low occupational stress, significantly had greater odds ratio (respectively 4,22 and 9,65; 95 % CI; p-value 0,00). Conclusion : An occupational stress is risk factors of subjective fatigue women workers in weaving loom unit PT. X. Keywords: Risk factor; subjective fatigue; occupational stress; women workers; weaving loom unit.